Enhancing penile function: the impact of a regenerative multimodal protocol on erectile dysfunction - Soto-Rodríguez, Andrés; Pastora-Sesín, Carla; Valverde-Espinoza, Juan Antonio; Campos-Sanchez, Sergio; Mauro-Stamati, Massimiliano; Giampapa, Vincent; Urzola, Víctor; Rojas-Solano, José Rafael (Frontiers in Reproductive Health, 2025)
BackgroundErectile dysfunction (ED) is a prevalent condition impacting men's quality of life and is often linked to cardiovascular and metabolic disorders. Conventional treatments like phosphodiesterase type 5 (PDE5) inhibitors could be ineffective for severe cases, indicating a need for innovative approaches. This study aimed to evaluate the efficacy and safety of a multimodal protocol combining low-intensity shockwave therapy (LiST), intrapenile and intravenous umbilical cord-mesenchymal stem cell (UC-MSCs) therapy, and hyperbaric oxygen therapy (HBOT) in men with ED. A retrospective pragmatic observational study was performed by reviewing medical records of 22 men treated at a private clinic in Costa Rica. Erectile function was measured using the Sexual Health Inventory for Men (SHIM) questionnaire before treatment and three months post-treatment.ResultsThe protocol significantly improved SHIM scores, with a mean increase of 3 points from baseline (p = 0.0017). No major adverse events were reported during follow-up.ConclusionThe multimodal protocol demonstrated a significant improvement in erectile function with a favorable safety profile, suggesting potential as a viable option for patients with ED. Further prospective randomized controlled trials are needed to validate these findings.